1998
DOI: 10.1128/cdli.5.2.199-204.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Previously Assigned Antibody Concentrations in Pneumococcal Polysaccharide Reference Serum 89SF by the Method of Cross-Standardization

Abstract: An enzyme-linked immunosorbent assay (ELISA) and the antibody concentrations assigned to different pneumococcal capsular polysaccharide types were used to estimate concentrations of antibody to additional pneumococcal types in reference serum 89SF and to confirm assigned antibody values. This was possible because the slopes of curves of antibody binding to all polysaccharide types evaluated (1, 3, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F) were similar. The point estimates for total anti-pneumococcal antibody an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…ELISAs were performed as described previously [17,18], with minor modifications to determine the concentration of specific anti‐capsular IgG to pneumococcal serotypes 6B, 14 and 23F. In brief, serum reference standards, quality control specimens and test specimens were adsorbed with a 1:50 dilution of a 10 mg/L preparation of cell‐wall polysaccharide (Statens Seruminstitut, Copenhagen, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…ELISAs were performed as described previously [17,18], with minor modifications to determine the concentration of specific anti‐capsular IgG to pneumococcal serotypes 6B, 14 and 23F. In brief, serum reference standards, quality control specimens and test specimens were adsorbed with a 1:50 dilution of a 10 mg/L preparation of cell‐wall polysaccharide (Statens Seruminstitut, Copenhagen, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…A reference pooled human serum sample was standardized by comparing it with the international standard serum 89-SF (a gift of Carl Frasch, Food and Drug Administration, Bethesda, Md. ), for which the concentrations of vaccine type-specific IgG antibody have been established for 15 of the 23 vaccine serotypes (6,24). Concentrations of specific IgG antibody in serum 89-SF for serotypes without established standard values were determined by a cross-standardization method (6): PPS 8, 5.74 g/ml; PPS 9N, 7.90 g/ml; PPS 10A, 5.41 g/ml; PPS 12F, 4.16 g/ml; PPS 15B, 14.20 g/ml; PPS 17F, 8.19 g/ml; PPS 22F, 5.48 g/ml; and PPS 33F, 7.69 g/ml.…”
Section: Subjectsmentioning
confidence: 99%
“…at 0.5 g per 100 l of phosphate-buffered saline per well by overnight incubation at 4°C. Because inspection of standard curves suggested that PPS 3 did not bind reproducibly to polystyrene plates, as suggested by others, plates were first coated with methylated albumin prior to capture with PPS 3, as described (6). All sera and standards were preadsorbed with cell wall polysaccharide (10 g/ml of serum; Statens Seruminstitut, Copenhagen, Denmark) at room temperature for 30 min.…”
Section: Subjectsmentioning
confidence: 99%
“…Table 3. Percentage agreement between the serogroup B microsphere assay and enzyme-linked immunosorbent assay (ELISA) using 0.2 and 0.25 mg mL À1 as the cut-off levels As the standard curve for serogroup B ran parallel to that of serogroups A and C, it was possible to assign a serogroup B IgM concentration (0.51 mg mL À1 ) to CDC 1992 using the method of cross-standardization (Concepcion & Frasch, 1998), thus allowing actual IgM concentrations to be derived.…”
Section: Discussionmentioning
confidence: 99%